Cracks in the ice: a digital health initiative disseminating evidence-based information about 'ice'. (20th October 2021) - Kershaw, S; Birrell, L; Champion, K; Duong, F; Grager, A; Stapinski, L; Newton, N; Kay-Lambkin, F; Teesson, M; Chapman, C
Abstract: Background: Crystal methamphetamine ('ice') causes significant societal harm and attracts a high level of concern in Australia. Cracks in the Ice (CITI: cracksintheice.org.au) is a digital public health initiative that was developed as part of a national response to concerns about ice. CITI is the first centralised national online portal for evidence-based information and resources about ice in Australia. It provides targeted information and resources for health workers, people who use ice, their family and friends, community groups and schools. CITI was developed collaboratively with input from drug and alcohol experts and over 500 Australian community members, including people with lived experience. A national online survey was conducted to evaluate whether CITI is meeting the needs of the Australian community. Methods: Eligible participants were Australian residents aged 18 years and over, and were recruited via the CITI website, email direct marketing, and social media. The survey assessed participants' perceptions of CITI (e.g., usability, navigation, utility) and their knowledge and attitudes about ice. Results: 2110 participants completed the survey, including people who use ice, affected family members, health workers, and general community members. Participants' response to CITI was overall positive and their knowledge of ice was generally good, but many held negative or stigmatising attitudes towards ice and people who use it. Conclusions: Digital public health initiatives stand to overcome structural, geographical, and attitudinal barriers to alcohol and other drug (AOD) prevention efforts. CITI ensures evidence-based information about the drug ice is readily available across all of Australia. Community evaluations have shown that CITI is meeting the needs of the Australian community. Key messages: Crystal methamphetamine ('ice') attracts a high level of concern in Australia. CITI is the first centralised national online portal for evidence-based information and resources about ice. Digital health initiatives stand to overcome structural, geographical, and attitudinal barriers to AOD prevention. Community evaluations ensure these initiatives meet the needs of their end-users.